Semantic Multimedia 4th International Conference on Semantic and Digital Media Technologies, SAMT 2009 Graz, Austria, December 2-4, 2009 Proceedings - Chua, Tat-Seng; Kompatsiaris, Yiannis; Mérialdo, Bernard; Haas, Werner; Thallinger, Georg; Bailer, Werner (Information Systems and Applications, incl. Internet/Web, and HCI, 2009)
This book constitutes the refereed proceedings of the 4th International Conference on Semantics and Digital Media Technologies, SAMT 2009, held in Graz, Austria, in December 2009. The 13 revised full papers and 8 short papers presented together with the abstracts of 2 invited keynote lectures were carefully reviewd and selected from 41 submissions. The volume discusses topics such as semantic analysis and multimedia, semantic retrieval and multimedia, semantic metadata management of multimedia, semantic user interfaces for multimedia, semantics in visualization and computer graphics, as well as applications of semantic multimedia.